Effect of laser on the bone defects healing in rats: An experimental study - Marković Aleksa; Dražić Radojica; Čolić Snježana (Serbian Medical Society - Dental Section, Belgrade, 2009)
Introduction. The stimulating effect of low-power laser on the process of wound healing is characterized by proliferation of fibroblasts, collagen production, and enhanced enzyme activity. The aim of this study was to evaluate the possible enhancing effect of low-power laser on the rate of the healing artificially created osseous defects in rats. Material and methods. Ten albino Wister rats were involved in this experimental study. Round defects (3 mm wide 2 mm deep) were made in each rat on both femurs. The right side was experimental while the left side was control. Osseous defects on the experimental side were daily treated with Galium, Aluminium, Arsenid (GaAlAs) low-power laser (Medicolaser 637, Technoline, Belgrade, Serbia), at the energy output of 4 J/cm2, with constant power density of 50 mW, and a wave length 637 nm (visible red light) per defect during seven days. Defects on the control side healed spontaneously. The effects of laser were evaluated two and three weeks postoperatively. Results. Histological analysis showed the powerful osteoblastic activity on the bone defects of the experimental side two weeks after surgery. On the control side, a new bone formation was noticed at the periphery of the bone defects but fibroblastic tissue with no signs of new bone was presented in the central areas. Three weeks after surgery, on the experimental side, bone defects were completely filled with spongious, lamellar bone while non-treated bone defects were characterized by mature lamellar bone at the peripheral areas and immature bone at the central areas. Conclusion. The results showed that the use of low-power laser could have a significant influence on the speed of curing bone defects in rats.